Ischemic stroke: Observations and analysis of stroke patients admitted in a tertiary hospital of Kathmandu - Shakya, Dipesh; Shrestha, Rabindra; Dhungana, Krishna; Kafle, Raisha; Bhatta, Sabnam (Journal of Kathmandu Medical College, 2019)
Background: Stroke is a disabling condition that has physical and mental impact on a patient’s life. Stroke is an important morbidity for low and middle income countries like Nepal. Hypertension, diabetes, smoking, and dyslipidemia are common risk factors in this regard and are inadequately controlled; mainly because of poor public awareness, inadequate infrastructure, lack of service and qualified manpower.Objectives: This study aims to provide insight into the epidemiology and risk factors in ischemic stroke patients.Methodology: A descriptive cross sectional study was conducted in 92 ischemic stroke patients at a tertiary care hospital Kathmandu Medical College and Teaching Hospital (KMCTH), Sinamangal, Nepal from December 2017 to June 2018. Consecutive sampling technique was used and data was collected from ischemic stroke patients above 14 years of age who were admitted in the Department of Neurology. Information regarding pre-morbid and morbid conditions, imaging findings as well as results was obtained from biochemical analysis of blood after taking consent from the patient or patient’s relative. Statistical Package for the Social Sciences Version 20 was used as a tool for statistical analysis.Results: Their mean age was 63.25 years with standard deviation of 16.45. Dyslipidemia was the most commonly found risk factor which was present in 77.2% of the subjects, followed by smoking (59.8%), presence of carotid artery atherosclerosis (59.8%), hypertension (50%), atrial fibrillation (26.1%) and diabetes mellitus(15.2%). Smoking was significant in males and heart disease was mostly seen in females.Conclusion: Dyslipidemia and smoking were the most common risk factors followed by carotid artery atherosclerosis. Patients with hypertension and dyslipidemia had higher incidence of stroke in both young and elderly group.